2022
DOI: 10.1109/tasc.2021.3137762
|View full text |Cite
|
Sign up to set email alerts
|

Design of a 60 kA Flux Pump for Fusion Toroidal Field Coils

Abstract: High-temperature superconducting (HTS) magnets offer a novel pathway to magnetically confined fusion energy generation. Reactor-scale fusion devices require tens of kA of current to generate large toroidal fields for magnetic confinement.Operating HTS magnets at kA-current levels is difficult due to unavoidable joint resistances that require active driving of current. The large footprint and energy demand of a solidstate power supply and multi-kA current leads present significant constraints on the size, cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…Operation at low temperatures would require very large current leads, but these current-ratings are not unrealistic for a high-field facility. An alternative approach is to supply the current using an HTS flux pump [30][31][32][33][34][35].…”
Section: Model Resultsmentioning
confidence: 99%
“…Operation at low temperatures would require very large current leads, but these current-ratings are not unrealistic for a high-field facility. An alternative approach is to supply the current using an HTS flux pump [30][31][32][33][34][35].…”
Section: Model Resultsmentioning
confidence: 99%
“…This may cause excessive heating, and unintentionally damage the switch. Additionally, it was recently shown that the power efficiency of flux-flow HTS transformer-rectifier flux pumps is improved by the ratio of the self-field to the applied magnetic field critical current κ = I c0 /I c (B a p p,⊥ ) [26]. In this case, the reduction of I c0 is expected to have a direct impact on the power efficiency of the device.…”
Section: Implications For Hts Switchesmentioning
confidence: 99%
“…Secondly, I c influences AC magnetic field switching, as the threshold field B th,⊥ decreases with larger fractions of I t /I c0 [16]. Finally, I c alters flux flow resistance by decreasing the current at which voltage is generated, while also limiting the power efficiency of switching [26]. Thus, understanding the critical current behavior of HTS switching elements using iron-core electromagnets is important for HTS flux-pump design.…”
Section: Introductionmentioning
confidence: 99%
“…Applications like flux pumping require relatively low voltage so it rules out electrical breakdown potential risk. For example, to charge the load coil of 60kA in 24 hour, a dc voltage of 55mV is required and only 6mV is needed to maintain a long-term steady current of 60kA [29].…”
Section: B Non-inductive Winding Structurementioning
confidence: 99%